2021
DOI: 10.3389/fneur.2021.704550
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 223 Targeting ATG16L1 Affects Microglial Autophagy in the Kainic Acid Model of Temporal Lobe Epilepsy

Abstract: This study aimed to explore whether microRNA (miR) 223 affects microglial autophagy by targeting autophagy-related 16-like 1 (ATG16L1) in the kainic acid (KA) model of temporal lobe epilepsy (TLE). The miRNA and mRNA expression levels were quantified using quantitative real-time polymerase chain reaction (qRT-PCR), and the protein expression was investigated using western blotting. A dual-luciferase reporter assay was used to test the direct interaction between miR 223 and ATG16L1. In situ hybridization was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…In this study, miR-132-3p levels were elevated and ATG16L1 decreased in the serum of epileptic patients and RA-treated SH-SY5Y cells, consistent with previous studies. ATG16L1 is an autophagic protein that is poorly expressed in epilepsy patients and animal/cell models that may promote autophagy and affect the progression of epilepsy [24]. In a kainic acid model of temporal lobe epilepsy, miR-223 affects microglia autophagy through ATG16L1 [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, miR-132-3p levels were elevated and ATG16L1 decreased in the serum of epileptic patients and RA-treated SH-SY5Y cells, consistent with previous studies. ATG16L1 is an autophagic protein that is poorly expressed in epilepsy patients and animal/cell models that may promote autophagy and affect the progression of epilepsy [24]. In a kainic acid model of temporal lobe epilepsy, miR-223 affects microglia autophagy through ATG16L1 [24].…”
Section: Discussionmentioning
confidence: 99%
“…ATG16L1 is an autophagic protein that is poorly expressed in epilepsy patients and animal/cell models that may promote autophagy and affect the progression of epilepsy [24]. In a kainic acid model of temporal lobe epilepsy, miR‐223 affects microglia autophagy through ATG16L1 [24]. miR‐223 also inhibits autophagy and facilitates central nervous system inflammation by targeting ATG16L1 [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some genetic sequencing studies for epilepsy patients and animal models suggest that the mutations in TBCK (encoding the TBC1-domain-containing kinase and inhibiting mTORC1 signaling), VSP15 (perturbing endosomal-lysosomal trafficking and autophagy flux), EPG5 (encoding a tethering factor that regulates the specific fusion of APs with late lysosomes/endosomes), SNX14 (encoding the sorting nexin family protein that mediating lysosome-AP fusion), ATP6V1A (encoding for the “A” subunit of the v1 sub-complex of V-ATPase, affecting lysosomal homeostasis and autophagy), ATP6AP2 (encoding a key regulator of v-ATPase, and its loss leads to lysosomal and autophagic defects), DMXL2 (encoding a member of the WD40 protein family that regulates v-ATPase trafficking and activity), or FAM134B (encoding the ER autophagy receptor) may contribute to the occurrence of epilepsy in space- and time-dependent manners [ 268 , 269 ] ( Table 1 ). Notably, recent studies have demonstrated that microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) involve the post-transcriptional regulation of autophagy-related proteins and the development of epilepsy pathophysiologies, such as miR-101, miR-181b, miR-134, miR-142, miR-421, miR-223, and Zinc finger antisense 1 (ZFAS1), metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), respectively [ 270 , 271 , 272 , 273 , 274 , 275 ]. Moreover, glia including astrocytes and microglia also plays a multi-faceted role in autophagy-mediated mechanisms that determine seizures and epileptogenesis [ 276 , 277 ].…”
Section: Epilepsy and Autophagymentioning
confidence: 99%
“…As previously mentioned for its role in neural autophagy, miR-223 has also been implicated in reducing neuroinflammation in microglia by targeting ATG16L [ 140 , 141 ]. Interestingly, it has been found that FOXO3a is yet another autophagy-related target of miR-223, with a negative correlation between the miR-223 levels and FOXO3a expression reported in several cell types [ 142 , 143 , 144 ].…”
Section: Specific Mirnas In Modulation Of Autophagy In Preclinical Mo...mentioning
confidence: 99%